EFEK PEMBELAJARAN METODE SIMULASI HANDS ONLY CPR TERHADAP PENGETAHUAN RESUSITASI JANTUNG PARU SISWA-SISWI DI SMAN 3 MATARAM - Alwan Wijaya (STIKES Mataram, 2019)
Adolescent is a period of transition from child to adult where changes occur in physic, mental and emotion. The older age, the more mature and stronger of a person will be thinking. Cardiac pulmonary resuscitation must be performed on every person found unconscious, not palpable and no breathing. The biggest prevalence of non communicable diseases, such as hypertension, coronary heart disease, heart failure, stroke in residents who live innthe urban areas, the disease has increased to 58% because of the lifestyle of urban people who tend to be at risk for non-communicable diseases above. This research is aimed at purpose of this study was to determine the effect of audiovisual Hands Only CPR on the level of knowledge of pulmonary heart resuscitation at SMAN 3 Mataram. The Population on this Study was 63 students of class X and XI. The sample were 50 people using purposive sampling method, with a Pre-experiment design study design with One Group peretest-postest design. The technique of collecting data using a questionnaire. Data analysis using the Willcoxon signed rank test . There is the effect of lerning methode Hands Only CPR simulation to the level of knowledge about pulmonary heart resuscitation in dealing with emergency situtations at SMAN 3 Mataram. There are other ways to increase knowledge of pulmonary heart resuscitation by demonstration using short course teaching aids, and counselling.